PENGARUH PEMBERIAN PUPUK NPK PHONSKA DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) - basilius payong; Abdullah Sarijan; Mariana L Resubun (Musamus University, 2022)
ABSTRACT This study aims to find out the effect of npk phonska fertilizer and cow manure on the growth and yield of eggplant plants (Solanum melongena L.). This study was carried out for 3 months, namely in March 2021 to June 2021 in Kamundu Village, Merauke Regency, using a random group design (RAK) with 7 treatments, 3 repetitions and 2 fertilizations. The results showed that the provision of NPK Phonska fertilizer had a real influence on plant height at the age of 7 DAP and 14 DAP, and on observations of the number of branches at the age of 21 DAP and 28 DAP. From the various treatments of NPK Phonska fertilizer and cow pen fertilizer, it can be seen that the number of fruits in the fertilization treatment of phonska is 100 kg / ha (E), fertilizing phonska 150 kg / ha (F), and fertilizing phonska 200 kg / ha (G) is above the average value with consecutive results of 11.21 fruits/plants, 12.54 fruits/plants, and 13.75 pieces/plants: while production that is above the average value is in the treatment of fertilizing phonska 150 kg/ha (F), and fertilizing phonska 200 kg/ha (G) with an average yield of 4.74 kg/plant and 5.57 kg/plant. Keywords: Phonska NPK fertilizer, manure, eggplant yield growth